Analisis Faktor-Faktor yang Memengaruhi Pendapatan Petani Mangga (Mangifera indica L.) di Desa Sumberjaya Kecamatan Tempuran Kabupaten Karawang - Mardiah, Aila Hayatul; Wulandari, Yeni Sari; Syahputra, Ali Fahmi (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Mango is one type of fruit that has high economic value and is popular in many countries, including Indonesia. According to data from BPS Karawang Regency, Tempuran District is one of the largest mango producers in Karawang Regency. The decline in mango fruit production in Tempuran Subdistrict is one of the problems in mango fruit cultivation which causes a lack of net income received by mango farmers. The purpose of this study is to determine the effect of land area, total production, selling price, labor, production costs, plant age and number of plants simultaneously and partially on the income of mango farmers. This research was conducted in Sumberjaya Village, Tempuran District, Karawang Regency. The research method used in this research is descriptive quantitative. The research data used are primary data and secondary data. Primary data used was obtained from interviews using a questionnaire. Secondary data used was obtained from books, journals, previous research reports and data from the Central Bureau of Statistics of Karawang Regency and related agencies. The sample was determined using the proportionate stratified random sampling method. The data analysis technique used was multiple linear regression analysis using SPSS 22. The results showed that the variables of land, amount of production, selling price, labor, production costs, plant age and number of plants had a significant influence simultaneously on the income of mango farmers. The variables of land, amount of production, and selling price partially have a significant positive effect. The variables of labor and production costs partially have a significant negative effect. The variables of plant age and number of plants partially do not have a significant influence on the income of mango farmers.